PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII B SMPS CENDANA PEKANBARU - Utari Ramadhanty; Armis '; Sehatta Saragih (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This classical research aims to improve learning process and to increase the mathematic learning evaluation by implying problem based learning model. Subjects of this research are VII B student at SMPS Cendana Pekanbaru of 2015/2016. Total number of participant are 21 whose academic achievement are heterogen. This research have 2 cycles, each have four stages: planning, implementation, observation, and reflection. Each cycles closed by daily exam. The data collected by observation and examination at daily based. The data analised by narative descriptive analysis and statistical descriptive analysis. The implementation succes if the improvement of the learning process and the number of students reach KKM increase at daily examination I and daily examination II. The research result from the observation form shows that teacher and student activity are good after the treatment implemented. More than half students actively participated in the learning process, as discuss, presented LAS, responded to presenter group, and gave the learning conclusion. The students also tried to solve the quiz from teacher in a great manner. The number of students whose achieved basic score of KKM,;daily examination I (first cycle), and daily examination II (second cycle) are 33.33%, 42.86% and 57.14%. This research shows that problem based learning model can improve learning process and increase mathematic learning evaluation for VII B Students at SMPS Cendana Pekanbaru.Key Words: Mathematic learning evaluation, Problem based learning, Classical research